Comparative evaluation of apical dye penetration of hydrophilic and hydrophobic obturation system: A stereomicroscopic study - Asit Vats; Umme Farva; Ajay Paliwal; Kshiti Bharadawaj; Harpreet Singh Chhabbra; Arohan Singh (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study is to evaluate the apical leakage of hydrophilic and hydrophobic obturation systems using a dye penetration method under stereomicroscope. Materials and Methods: Sixty freshly extracted human single-rooted mandibular incisors were decoronated and standardized to a working length of 16 mm. Root canal preparation was done with rotary ProTaper file system in all samples. The teeth were randomly divided into three groups (20 each) and obturation was done. Group A was obturated using gutta-percha (GP)/AH Plus (hydrophobic), Group B using Resilon/Epiphany system (hydrophilic), and Group C using SmartSeal system (hydrophilic). The linear apical dye leakage was measured using methylene blue dye under stereomicroscope. Statistical Analysis: Statistical analysis was performed using SPSS version 21.0. Kruskal-Wallis test (nonparametric ANOVA) was used for intergroup comparisons. Between-group comparisons were made using Mann-Whitney U-test was done. Results: All three groups showed dye leakage. Intergroup comparison exhibited statistically significant difference among the groups. GP with AH Plus showed a highest dye leakage value. Conclusion: The sealing to apical leakage shown by hydrophilic obturation systems was significantly better as compared to hydrophobic obturation systems, though none of the obturation systems were found out to be completely devoid of leakage.